2020
DOI: 10.1136/bmjopen-2019-036397
|View full text |Cite
|
Sign up to set email alerts
|

Healthy eating and physical activity environments in out-of-school hours care: an observational study protocol

Abstract: IntroductionChildcare settings have been widely identified as important venues for promoting healthy lifestyles to children. Out-of-school hours care (OSHC) is a rapidly growing childcare service, yet there has been limited research reported on healthy eating and physical activity (HEPA) environments within the Australian OSHC setting. This research aims to describe the HEPA environments related to foods and beverages served, staff behaviours and child physical activity levels across two local health districts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The ActiGraph WGT3X-BT sensors, used in this study to quantitatively measure sleep values and physical activity levels at school age, have been widely used in research and have demonstrated reproducibility, validity and feasibility for children and adolescents [13,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…The ActiGraph WGT3X-BT sensors, used in this study to quantitatively measure sleep values and physical activity levels at school age, have been widely used in research and have demonstrated reproducibility, validity and feasibility for children and adolescents [13,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…OSHC service staff and parents were notified of the study via OSHC internal communication avenues and all information relating to this study was displayed at each OSHC service for a minimum of two weeks prior to data collection and during the data collection period. A detailed methodology has been previously published [22].…”
Section: Sample Selection and Recruitmentmentioning
confidence: 99%